Nice rice wins a prize - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Farmers in West Africa prefer local rice varieties for their taste and adaptability to local pests, drought spells and soil conditions. However, these varieties hardly yield enough to cover home consumption, let alone a surplus to sell at the...